2010
DOI: 10.1186/1687-9856-2010-740629
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Percutaneous Epiphysiodesis Operation around the Knee to Reduce Adult Height in Extremely Tall Adolescent Girls and Boys

Abstract: Objective. The aim was to determine efficacy and safety of a surgical method to reduce adult height in extremely tall adolescents. Methods. Data for all girls (n = 12) and boys (n = 9) in our center subjected to bilateral percutaneous epiphysiodesis around the knee who had reached final height were included. Final height predictions were based on hand and wrist X-rays before surgery. Results. When compared to prediction, adult height was reduced by 4.1 ± 0.7 cm in treated girls (P < .001) and 6.4 ± 0.7 cm in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…There are two smaller studies on treatment effect of PE, showing similar results. Benyi et al 2 reported a mean reduction of 4.1±0.7 cm in 12 girls and 6.4±0.7 cm in 9 boys. Odink et al 1 reported a mean reduction of 7.0 cm (range 1.2–13.8 cm) in 15 tall boys.…”
Section: Discussionmentioning
confidence: 94%
“…There are two smaller studies on treatment effect of PE, showing similar results. Benyi et al 2 reported a mean reduction of 4.1±0.7 cm in 12 girls and 6.4±0.7 cm in 9 boys. Odink et al 1 reported a mean reduction of 7.0 cm (range 1.2–13.8 cm) in 15 tall boys.…”
Section: Discussionmentioning
confidence: 94%
“…There are alternatives to pharmacological treatment for CTS. Benyi et al (14) reported a height reduction, compared to prediction, of 4.1 cm in 12 girls subjected to bilateral percutaneous epiphysiodesis. No side effects except postoperative pain were reported.…”
Section: Articlesmentioning
confidence: 96%
“…EE2 treatment of extreme tall stature has become increasingly debated and controversial. In Sweden, percutaneous epiphysiodesis operation is suggested as an alternative to EE2 treatment (14). In our center, we introduced an alternative clinical practise 20 y ago, when we introduced early treatment with oral administration of natural estrogens (17β-estradiol (E2)).…”
Section: Articles Upners and Juulmentioning
confidence: 99%
“…Others have recommended that the intervention should be performed at a bone age not exceeding 12.5 years in girls and 14 years in boys, and that a treatment decision should be taken before girls have reached a height of 170 cm and boys 185 cm. A potential side-effect is the development of leg length discrepancy although in a recent series this was not observed 21. This intervention remains controversial and further data on its safety profile are required.…”
Section: Interventions Aimed At Limiting Final Height Prognosismentioning
confidence: 99%